Analysis Of Factors That Influence Purchase Intentions For Skintific Products Using Tiktok Shop Indonesia With Online Trust As Mediator Variable - Bhra Ciptaning Sekarlingga; Arif Hartono (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to test and analyze the influence of brand awareness, competitive price, information quality, and product delivery on brand trust and online purchase intentions for Skintific products through the TikTok Shop platform. The research approach used is quantitative. Data collected by distributing online questionnaires via Google Form. The sampling technique used non-probability sampling and purposive sampling method. The method used in this study is PLS- SEM, using the SmartPLS statistical software tool. Data analysis techniques used in this study are descriptive analysis and statistical analysis. The results of this study are brand awareness has a positive and significant effect on brand trust, but it has no effect on online purchase intention. Information quality has a positive and significant effect on brand trust. Product delivery has a positive and significant effect on brand trust. Competitive price has a positive and significant impact on purchase intentions, and brand trust has a positive and significant effect on online purchase intentions.